(22x+88)=(52-2x)

Simple and best practice solution for (22x+88)=(52-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (22x+88)=(52-2x) equation:



(22x+88)=(52-2x)
We move all terms to the left:
(22x+88)-((52-2x))=0
We add all the numbers together, and all the variables
(22x+88)-((-2x+52))=0
We get rid of parentheses
22x-((-2x+52))+88=0
We calculate terms in parentheses: -((-2x+52)), so:
(-2x+52)
We get rid of parentheses
-2x+52
Back to the equation:
-(-2x+52)
We get rid of parentheses
22x+2x-52+88=0
We add all the numbers together, and all the variables
24x+36=0
We move all terms containing x to the left, all other terms to the right
24x=-36
x=-36/24
x=-1+1/2

See similar equations:

| 9(x-4)+5=3(x-1)+8 | | (52-2x)=(22x+88) | | (7x-10)=(12x) | | -7x+13=69 | | 0.75(m-20)=60 | | X+(18x)=160 | | -8g-5=-5(3g-3) | | -10.8=-1.2+v/6 | | 4-9v=-23 | | 7x+17-4x=5x-5 | | -8.8=3(3x-1)-9.8x | | 39=124x | | -8(h+11)=40 | | -3(e-5)=21 | | -7(6-h)=14 | | 2m-4=+3m-6 | | -11(5+w)=121 | | (x^2-x-6)/(2x^2+x-6)=0 | | 4^(3x-5)=26 | | 2x+6+3x-26=90 | | -9x-45=54 | | u-39=9 | | 5e=1 | | 26y+2(60-7y)=180 | | (x+50)(x+20)=400 | | 1=4/1c | | -3/7v-1/2=-3/5 | | 3(w-3)=w+5-4(-3w-1) | | 8x-10=3x+3=180 | | 2x-8+2(6x+5)=-2(x+8) | | -2(7x-8)+x=3(x+8) | | 4(u-4)-6=-5(-3u+2)-3u |

Equations solver categories